Dynamic Voltage Restorer as a Solution to Voltage Problems in Power Systems: Focus on Sags, Swells and Steady Fluctuations - Nhlanhla Mbuli (Energies, 2023)
In this study, the author presents the results of a survey on the utilisation of a dynamic voltage restorer (DVR) in power systems to alleviate voltage problems that result in sags, swells and fluctuations in voltage outside the required steady limits. A methodology based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement is adopted for conducting and reporting on the review, while the Scopus database is used to locate the relevant publications. A total of 68 publications qualify for inclusion in the survey. A bibliometric analysis covering the number of publications per annum, the top 10 most-cited journals and the top 10 most-cited publications is performed. The information from the selected publications is extracted, summarised and categorised into network scenarios for the use of DVRs, topologies and optimisation of DVRs; strategies for DVR controllers; and platforms that evaluate the feasibility of DVR topologies and controllers. Moreover, research trends and gaps are evaluated. Finally, potential areas for future research are proposed. This study provides an overview of the research on the use of a DVR to resolve voltage problems and is a resource for researchers generally interested in distributed flexible AC transmission systems (DFACTSs) and particularly interested in DVRs.